Screening for oral cancer utilising risk-factor analysis is ineffective in high-risk populations. Issue 1 (January 2021) - Lalli, A.; Aldehlawi, H.; Buchanan, J.A.G.; Seoudi, N.; Fortune, F.; Waseem, A.
Abstract: Screening for oral cancer by direct visual examination is believed to be ineffective because of the difficulty in differentiating a small number of malignancies from the much more prevalent benign oral mucosal lesions (OML) that are found in high-risk individuals. Standardised clinical diagnoses were recorded for all the OMLs identified during oral visual examination of 1111 individuals with risk factors for oral cancer, including tobacco and areca nut (paan) consumption. Suspicious lesions were referred for biopsy and definitive diagnosis. A total of 1438 OMLs with 32 different clinical diagnoses were identified in 604 participants. Analysis of referrals revealed two distinct groups: visually benign lesions (VBLs) none of which was referred, and visually complex lesions (VCLs) comprising 661 OMLs with nine different clinical diagnoses. After biopsy the VCLs included known potentially malignant disorders (PMDs) as well as benign lesions such as paan mucositis. VCLs (but not VBLs) share risk factors with oral cancer (p < 0.05 for paan 5.82 (CI: 1.98 to 8.43), and smoking 3.59 (CI: 1.12 to 4.47)). They are clinically indistinguishable from, but much more prevalent than, oral cancer, and most will never undergo malignant change. They therefore can prevent dentists from accurately detecting malignancy during the clinical examination of high-risk patients. However, they can easily be differentiated from other benign lesions by visual examination alone. Further research into diagnostic technology is needed to help differentiate them from oral cancers.